2014
DOI: 10.18870/hlrc.v4i2.177
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Students in by Sending Them out: Retention and Service-Learning

Abstract: <p>This review of recent literature examines the research on the impact of service-learning on student retention.  The theoretical framework of the review draws on both Tinto’s model of student attrition and Knowles’s theory of adult learning, which together suggest that academic and social integration, active participation and engagement in learning, and application and relevancy of the subject-matter under study are key factors in student success. The role of these factors has been confirmed in a growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There are several examples of studies that examined the influence of adult learning theory on student outcomes. Based upon the research of Tinto and Knowles, Yob (2014) promoted active participation and engagement of learning through service learning.…”
Section: Perspectives or Theoretical Frameworkmentioning
confidence: 99%
“…There are several examples of studies that examined the influence of adult learning theory on student outcomes. Based upon the research of Tinto and Knowles, Yob (2014) promoted active participation and engagement of learning through service learning.…”
Section: Perspectives or Theoretical Frameworkmentioning
confidence: 99%
“…1 Iris Yob has examined the role of higher education generally and music education specifically in creating positive social change. 2 At times, and against the backdrop of recent writing on music education, social change, and social justice, 3 we each have explored topics in the other's area of interest. 4 Neither of us has systematically brought together the two themes: building practices on grounding metaphors for developing music education as a means for promoting the common good.…”
Section: Metaphors For a Change: A Conversation About Music Education...mentioning
confidence: 99%
“…Servicelearning courses in high school and undergraduate programs, which connect what is studied in class with working on real-world problems in the community, have a 3-decade history now and substantial literature that provides evidence of their powerful impact on learners. This includes, for instance, studies that found that service-learning increased a student's engagement with the community outside of the university, their greater understanding of issues and problems in the community, a deeper appreciation of and ability to relate to cultural and racial difference, an enhanced belief in their ability to make a difference, a profounder commitment to community service, and a stronger tendency to choose helping careers (Gallini & Moely, 2003) and student retention (Yob, 2014).…”
Section: Applicationmentioning
confidence: 99%